2013
DOI: 10.5324/fn.v32i0.1438
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and patterns of spread of recolonising Eurasian beavers (Castor fiber Linnaeus 1758) in fragmented habitat, Agdenes peninsula, Norway

Abstract: The Agdenes peninsula, Sør-Trøndelag, Norway, 1060km2, is a heavily dissected mountainous landscape with numerous small watersheds, of mainly steep gradient, flowing separately into the sea or to fjords. Suitable habitat for permanent beaver occupation occurs mainly as isolated patches within these watersheds. Eurasian beavers were directly reintroduced to the area in 1926 and 1928. The last known individual of this population died in 1961. In 1968-69 2 pairs and a young animal were reintroduced on the Ingdals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Beavers are also advancing slowly into the region along the coast, both from the south and north. Colonisation patterns indicate dispersal through brackish and salt water, especially where it is sheltered (Halley et al 2013).…”
Section: History and Status Of Beaver Populations By Countrymentioning
confidence: 99%
“…Beavers are also advancing slowly into the region along the coast, both from the south and north. Colonisation patterns indicate dispersal through brackish and salt water, especially where it is sheltered (Halley et al 2013).…”
Section: History and Status Of Beaver Populations By Countrymentioning
confidence: 99%
“…). Streams with <15% gradient (Beier & Barrett , Maringer & Slotta‐Bachmayr ). Not in marine/tidal sections (Halley et al. ).…”
Section: The Key Issuesmentioning
confidence: 99%
“…Beavers do not utilise marine waters extensively, but there is evidence of beavers dispersing along coastlines in Norway (Halley et al. ), Denmark (Thomas Borup Svendsen pers. comm.…”
Section: The Key Issuesmentioning
confidence: 99%
“…Thus, our results indicate that lack of high-quality habitats in the novel areas has not restricted the spread of Eurasian beavers from the original area. Other studies have shown that beavers usually occupy the most optimal habitats first (Halley and Rosell 2002;John et al 2010;Halley et al 2013), resulting to distant and irregular colonization patterns (Fustec et al 2001), but often stay close to their natal territory if there are suitable habitats available (Hartman 1994a).…”
Section: Differences In Habitat Use In the Original And Novel Areas Of The Eurasian Beavermentioning
confidence: 99%